EVALUATION PHYTOCHEMICAL SCREENING, ANALGESIC AND ANTI-INFLAMMATORY ACTIVITY (SYNERGIC ACTIVITY) OF HYDROALCOHOLIC EXTRACT OF COCCONIA GRANDIS - CHANDAKA MADHU; RAMANJANEYULU M (International Journal of Pharma and Bio Sciences, 2013)
In the present study, the anti-inflammatory and analgesic effect of the hydroalcoholic extract of coccinia grandis whole plant was investigated. The hydroalcoholic extracts of coccinia grandis whole plant were ingested orally (p.o.) in two different doses, 200 and 400 (mg/kg body weight). The anti-inflammatory effect of coccinia grandis was tested in: carrageenan-induced paw oedema in wistar albino rats and compared with the standard, diclofenac (10 mg/kg body weight). The analgesic effect of the hydroalcoholic effect of coccinia grandis was evaluated in Swiss albino mice by usingEddys hot plate method and compared with the standard, aspirin (25 mg/kg body weight). The results showed that coccinia grandis has significant reduction (p.0.01) in inflammation (200 mg/kg body weight) and (400 mg/kg body weight) as compared to the standard drug, diclofenac. In assessing analgesic effects, there is a significant (p<0.01) reduction in the paw licking for (400 mg/kg) and diclofenac (10 mg/kg) when compared to control. These results expressing that the extracts would possess analgesic and anti-inflammatory properties. All these effects and the changes in the behavioural activities could be suggested as contributory effects to the use of coccinia grandis whole plant in the management of inflammation and painful conditions.